Collaborative learning strategy with simultaneous rooms on google meet - Soares Rocha da Silva, Andréa (2022)
Information and Communication Technologies (ICT) were the main tools used during the Pandemic in remote teaching strategies, given the impossibility of face-to-face classes. In this context of social isolation, Google tools such as Google Meet, Google Forms, among others, were widely used. The present work consists of the report of the experience lived by the five authors, who, in a collaborative and remote way, planned and produced an online workshop, which was given by them in an international event in the area of Information Science. The workshop aimed to train the participants for the collaborative production of didactic resources in digital format. For this, after an initial explanation, the participants were divided into groups through Google Meet breakout rooms, each of the rooms being moderated by a different facilitator. Each group learned how to use a different tool (Canva, PowerPoint online, Google Forms, and Google Sites), and in the end presented the resource they had developed. The experience was considered successful by both participants and facilitators. The facilitation strategy, using an active, constructionist methodology, was made possible by Google Meet's breakout rooms, allowing different tools to be explored simultaneously by the groups attending the workshop. However, the participants regretted the little time available to experience the tools used by the other groups.